(NoSNOWY KWANTOWOJ MEHANIKI (B:s (Nu^EBNOE POSOBIE (B/s - (NbLOHINCEW(B, (NdMITRIJ iWANOWI^s ((NsANKT(B-(NpETERBURGs (NmOSKWAs (NkRASNODAR (B:s (NlANX(B,s, 2004)
(NpOSOBIE PREDNAZNA^ENO DLQ STUDENTOW(B-(NFIZIKOW I NAU^NYH RABOTNIKOW(B.s
Keywords: (NkWANTOWAQ MEHANIKAs; (NfIZIKAs; (NtEORETI^ESKAQ FIZIKAs